Teaching community engagement for health professions students in underserved areas - Ivan Gomez; Virginia Fowkes; Iris Price (Discover Education)
Abstract Community engagement concepts incorporated into service-learning experiences help students in the health professions to connect classroom work with clinical practice and learn strategies and skills to improve community health. Service learning improves team skills, allows students to gain knowledge about communities where they train, and connects them with role models and mentors, which are benefits that may eventually affect their career choices. The California Statewide Area Health Education Centers (AHEC) Program requires students to conduct a community project with a medically underserved population through its AHEC Scholars Program in Community Health, guided by a structured curriculum. The program’s curriculum provides guidelines for the process and reporting of community projects. Between 2018 and 2023, 318 health professions students from 14 disciplines conducted 253 individual or group projects in medically underserved sites. These projects focused on community education, teaching fellow students, patient education, quality improvement in community health centers, and other health-related topics. The outputs from these students’ projects supplied educational information and resources for patients, health centers, community groups, and other students. Several of the projects were interdisciplinary with students from different health disciplines working collaboratively to implement the projects. All participating students reported having positive experiences and engagement with their communities. Two University of California medical schools adopted the AHEC Scholars curriculum as required or elective opportunities in community health. Practice sites and educational institutions benefited from this work as well. This model offers a promising framework for other educational institutions that provide training in underserved communities.